SYIAH: POLITIK ATAU AGAMA? (Studi Analisis Perspektif Muhibuddin Al-Khatib) - Muslih, M Kholid; Moh Shobirin, Munar; Dhiaul Fikri, Muhammad; Mahbubah, Khotimatul; Kaffah, Silmi (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2022)
Judging from the history of the emergence of Shia there are different views of Shia leaders. Some say that the early emergence of Shi'ism was just a political movement. This is seen by the support for Sayyidina Ali as caliph after the death of the Prophet. Another opinion states his appearance as a supporter and follower of Sayyidina Ali in the battle of Jamal and Shiffin. However, it is different from a contemporary thinker who wrote about Shi'ism in the book Al-Khututh al-'Aridhah Li Dini al-Syi‘ah, namely Muhibuddin al-Khatib. Departing from the contradiction of the emergence of Shi'ism itself, this paper aims to explore the opinion of Muhibuddin al-Khatib. This research is a qualitative study of literature. Sources of data were obtained from books, journals, articles, and everything relevant to this research. This research method uses a comparative method of the opinion of Shia leaders. As for the results of this research, according to Muhibuddin al-Khatib, the early emergence of Shiites in the first period was political and not religious, where the imams of the Ahl al-Bayt handed over all rights to all people in terms of power and deliberation, as well as the rights of all Muslims in choosing and nominating who entitled to the caliphate. However, there is an evolution in Shiite thought about the transformation of Shiite groups from politics to religion by the